2015
DOI: 10.1103/physrevlett.115.074502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Droplet Removal from Hydrophobic Fiber-Based Coalescers

Abstract: Fiber-based coalescers are widely used to accumulate droplets from aerosols and emulsions, where the accumulated droplets are typically removed by gravity or shear. This Letter reports self-propelled removal of drops from a hydrophobic fiber, where the surface energy released upon drop coalescence overcomes the drop-fiber adhesion, producing spontaneous departure that would not occur on a flat substrate of the same contact angle. The self-removal takes place above a threshold drop-to-fiber radius ratio, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 27 publications
8
103
0
Order By: Relevance
“…[1][2][3][4][5] Extensive research efforts have been devoted to promote dropwise condensation of water by employing various surface chemistries and micro-/nano-textures. [2][3][4][5][6][7][8][9][10] While recent studies have shown that droplet growth on millimetric convex surfaces by condensation is facilitated, [11][12][13] a more detailed study on droplet growth on textured surfaces is required to systematically understand the impact of the sign and the magnitude of the radius of curvature of surface features. Here, we provide a quantitative analysis of droplet growth dynamics on hydrophobic surfaces with a wide range of millimeter-scale surface topographies ranging from convex textures (e.g., bumps) to concave textures (e.g., dimples).…”
Section: Main Textmentioning
confidence: 99%
“…[1][2][3][4][5] Extensive research efforts have been devoted to promote dropwise condensation of water by employing various surface chemistries and micro-/nano-textures. [2][3][4][5][6][7][8][9][10] While recent studies have shown that droplet growth on millimetric convex surfaces by condensation is facilitated, [11][12][13] a more detailed study on droplet growth on textured surfaces is required to systematically understand the impact of the sign and the magnitude of the radius of curvature of surface features. Here, we provide a quantitative analysis of droplet growth dynamics on hydrophobic surfaces with a wide range of millimeter-scale surface topographies ranging from convex textures (e.g., bumps) to concave textures (e.g., dimples).…”
Section: Main Textmentioning
confidence: 99%
“…Second, the energetic model typically calculates the launching speed by assuming a perfect capillary-inertial energy conversion, an assumption that does not hold for a related phenomenon of coalescence-induced jumping drops. When pure liquid drops jump upon coalescence, the released surface energy is converted into translational kinetic energy with wide-ranging efficiencies, from 4% to 40% [19][20][21]. Third, the two-stage launching process outlined above is essentially a rigid-body model and cannot represent the true launching mechanism induced by liquid drop coalescence.…”
Section: Energetic Modelmentioning
confidence: 99%
“…Inspired by nature, [ 4–7 ] superhydrophobic surfaces with extreme repellency to water have attracted significant interest, owing to their potential applications in anti‐condensation, anti‐frosting, anti‐icing, anti‐fogging, and self‐cleaning activities. [ 8–20 ] Biomimetic superhydrophobic surfaces can be prepared via different approaches, including reactive ion etching, [ 21 ] chemical/physical processing, [ 22–25 ] lithographing, [ 26,27 ] and coating. [ 28–33 ] Among these approaches, the coating approach has been widely applied, owing to its simple preparation process, low equipment requirement, and wide application range.…”
Section: Introductionmentioning
confidence: 99%